IMPLEMENTASI KONTEKS ETNOMATEMATIKA DALAM PEMBELAJARAN DIMENSI TIGA MENGGUNAKAN STRUKTUR BANGUNAN TRADISIONAL SUKU BATAK - Indra Risky Mahesa; Naila Fauziah; Tamrin Manurung; Ellis Mardiana Panggabean; Tua Halomoan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the implementation of an ethnomathematical approach in teaching three-dimensional geometry using the structure of Batak traditional houses as a local cultural context. Employing a descriptive qualitative method, data were collected through classroom observations, teacher and student interviews, visual documentation, and pre- and post-tests. The findings indicate that using Batak traditional architecture as a learning medium positively impacts students' understanding of volume, surface area, and composite solid shapes. Students showed a significant improvement in post-test scores and greater engagement and enthusiasm during the learning process. The learning became more meaningful as it connected abstract mathematical concepts with students’ socio-cultural realities. However, challenges remain, particularly in media availability and contextual limitations outside specific cultural settings. Overall, the ethnomathematical approach proves to be an innovative strategy to bridge formal mathematics and local cultural heritage.